Public Relations Management in Shaping Organizational Behavior at Madrasah Aliyah - Salam, Abdul; Santoso, Didik; Nasution, Inom (AL-ISHLAH: Jurnal Pendidikan, 2024)
Public relations (PR) management is vital in shaping organizational behavior, especially in educational settings. This study examines the PR management framework at Madrasah Aliyah Negeri (MAN) 3 Medan, focusing on how PR practices contribute to improving organizational behavior. A descriptive qualitative approach was used, involving data collection through observations, interviews, and documentation. The data were analyzed using the Miles and Huberman model, which includes data reduction, display, and conclusion drawing. Triangulation was applied to ensure the accuracy of the findings. The study found that PR management at MAN 3 Medan is built around key components: planning, implementation, communication systems, organizational supervision, special events organization, media use, and PR program evaluation. These components enhance organizational behavior by enabling effective feedback communication, securing community support, and aligning organizational goals with community expectations. The findings suggest that strong PR management significantly improves organizational behavior in educational institutions. This framework not only strengthens internal operations but also enhances the institution's relationship with the community. Feedback mechanisms and community support are essential indicators of successful PR management. In conclusion, the study shows that implementing a well-structured PR management framework at MAN 3 Medan positively impacts organizational behavior. This is reflected in better communication, stronger community engagement, and the achievement of organizational goals. The study highlights the crucial role of PR management in promoting organizational development in educational institutions.